Proceedings of the Boston Area Colloquium in Ancient - Monserrat Molas, Josep (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Philosophy (edited by John Cleary & Gary M. Gurtler, S.J., Leiden- Boston: Brill, 2003). 332 pp.